Evaluation of Tourism Village Development Program: Comparative Study of Lebak Regency and Ende Regency Tourism Villages - Adriwati, Adriwati; Ahmad, Alisya Fadillah; Karunia, Luki (KnE Social Sciences, 2025)
This research aims to evaluate tourism village development program in Lebak Regency and Ende Regency using a descriptive qualitative approach with a case study method. Data were collected using free guided interviews, observation, and reviewing documents, and were analyzed qualitatively. Tourism villages in Lebak Regency were formed to empower village communities and be direct actors in increasing readiness and awareness in addressing tourism potential and attraction. Each village compiles an event agenda that prioritizes local wisdom in their village. The Tourism Awareness Movement in all areas of Lebak Regency is realized through the existence of Tourism Awareness Groups (Pokdarwis) as actors driving tourism. Tourism attractions in Lebak Regency are grouped into three parts of natural, cultural, and artificial attractions. As for Ende Regency, the direction of the development of the tourism area uses a cluster system approach to explore, strengthen, and optimize potential and overcome specific problems. Thus, it is expected that the development of tourism areas can be more focused, specific, and still have a character in accordance with local values. Ende Regency has the advantage of tourism based on its natural resources with their authenticity and sustainability, local cultural resources, as well as the principle of maximum benefit for humanity, society, culture, and environment.